2011
DOI: 10.1086/662029
|View full text |Cite
|
Sign up to set email alerts
|

Floral Herbivory Affects Female Reproductive Success and Pollinator Visitation in the Perennial Herb Alstroemeria ligtu (Alstroemeriaceae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.Floral damage can reduce flower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The majority of flowering plants are involved in one or more intimate interactions with pollinators, and disruption of plant-pollinator interactions can be directly detrimental for plant fitness (Ollerton, Winfree, & Tarrant, 2011;Wilcock & Neiland, 2002). A number of studies have identified disruptions in plantpollinator interactions due to plant responses to insect herbivores (Hoffmeister, Wittköpper, & Junker, 2016;Liao, Gituru, Guo, & Wang, 2013;Schiestl, Kirk, Bigler, Cozzolino, & Desurmont, 2014), with consequences for plant reproduction (Botto-Mahan et al, 2011;Chautá, Whitehead, Amaya-Márquez, & Poveda, 2017;Rusman, Lucas-Barbosa, & Poelman, 2018).…”
mentioning
confidence: 99%
“…The majority of flowering plants are involved in one or more intimate interactions with pollinators, and disruption of plant-pollinator interactions can be directly detrimental for plant fitness (Ollerton, Winfree, & Tarrant, 2011;Wilcock & Neiland, 2002). A number of studies have identified disruptions in plantpollinator interactions due to plant responses to insect herbivores (Hoffmeister, Wittköpper, & Junker, 2016;Liao, Gituru, Guo, & Wang, 2013;Schiestl, Kirk, Bigler, Cozzolino, & Desurmont, 2014), with consequences for plant reproduction (Botto-Mahan et al, 2011;Chautá, Whitehead, Amaya-Márquez, & Poveda, 2017;Rusman, Lucas-Barbosa, & Poelman, 2018).…”
mentioning
confidence: 99%
“…Reductions in pollinator visitation to damaged flowers and plants are likely due to reduced visual attractiveness (e.g., fewer flowers per inflorescence, changes in floral symmetry), as well as changes in the rewards provided to pollinators (Krupnick et al, 1999). For example, the removal of tepal tissue from Alstroemeria ligtu Curtis (Alstroemeriaceae) changed the pattern of UV reflectance of nectar guides and subsequently decreased pollinator visitation (Botto‐Mahan et al, 2011). Although we did not measure floral traits in our study, we hypothesize that flower size and shape were important for pollinators in making the initial decision to forage on plants.…”
Section: Discussionmentioning
confidence: 99%
“…If florivory damage indeed affected visitation rates by pollinators in manzanita as it does in other systems (Botto-Mahan et al 2011; Cardel and Koptur 2010; Cascante-Marin et al 2009; Ferreira and Torezan-Silingardi 2013; Liao et al 2013; Sober et al 2010; Zangerl and Berenbaum 2009), and since in manzanita nectar robbers and pollinators are not necessarily systematically distinguishable (Richardson and Bronstein 2012), it is possible that nectar robbers could be deterred by florivory damage. Since the prevalence of floral perforation was much higher during the end of the flowering season, it is not surprising that it was that time when flowers were more likely to bear both kinds of perforations.…”
Section: Discussionmentioning
confidence: 99%